Evidence of Strict Stereospecificity in the Structure of sn‐1, 2‐Diacyl‐3‐Acetyl‐Glycerols from Euonymus maximowiczianus Seeds Using Nuclear Magnetic Resonance Spectroscopy. Issue 4 (2nd May 2018) - Sidorov, Roman A.; Shashkov, Alexander S.; Solovyev, Pavel A.; Gorshkova, Elena N.; Tsydendambaev, Vladimir D.
Abstract: Asymmetric, optically active sn ‐1, 2‐diacyl‐3‐acetyl‐glycerols ( Ac DAG) have been known to scientists for several decades. However, to date, the problem of their structure has not been definitely resolved, which has led to a vast diversity of terms used for their designation in the literature. Using two‐dimensional nuclear magnetic resonance, we have investigated Ac DAG from the mature seeds of Euonymus maximowiczianus, from which we have been able to both identify a correlation of the methyl group in acetic acid residue with protons at the carbon atom at sn ‐3 position in the glycerol residue of the Ac DAG molecule and, for the first time, demonstrate that this correlation is observed exclusively with one carbon atom at the α‐position, but not with two as would have been expected in case of a racemic mixture. Moreover, results of our analysis of Ac DAG isolated from the seeds of E. maximowiczianus directly confirm that diacylglycerol‐3‐acetyl‐transferase is responsible for their biosynthesis, which reveals a strict specificity not only to acetyl‐CoA as one of the substrates but also to the sn ‐3‐position of the glycerol residue in sn ‐1, 2‐diacylglycerol during their biosynthesis.